Pengembangan Buku Suplemen Digital Geografi bermuatan ayat-ayat Al-Qur’an pada materi tata surya untuk MA - Fika Damayanti; Yuswanti Ariani Wirahayu; Djoko Soelistijo; Budi Handoyo (Universitas Negeri Malang, 2023)
The demands of teaching materials today lead to digital forms. One of the things that can be pursued is through the development of a digital supplement book. This study aims to produce a digital Geography supplement book that is correlated with the Qur'an on solar system material that is practical and easy for Madrasah Aliyah students. This research method is the development of the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Using quantitative and qualitative data types. Quantitative data acquisition through a questionnaire with a Likert scale. While qualitative data obtained through criticism and suggestions from material experts, media, Al-Qur'an and research subjects. This digital supplement book was tested on 25 students covering grades X, XI, and XII IPS 1 MA Plus Al Amin Abung Surakarta, North Lampung. The results of the development of digital geography supplement books from material experts got a percentage of 88 percent, media experts 98 percent, and Al-Qur'an experts 92 percent. While the teacher's response got a percentage score of 92 percent and students with a score of 91 percent. These results show that the development of a digital geography supplement book containing verses of the Qur'an on solar system material is very feasible so that it can be used in Geography learning. Tuntutan bahan ajar saat ini mengarah pada bentuk digital. Salah satu yang bisa diupayakan yakni melalui pengembangan buku suplemen digital. Penelitian ini bertujuan menghasilkan buku suplemen Geografi digital yang dikorelasikan dengan Al-Qur’an pada materi tata surya yang praktis serta mudah untuk siswa Madrasah Aliyah. Metode penelitian ini adalah pengembangan model ADDIE (Analyze, Design, Development, Implementation, Evaluation). Menggunakan jenis data kuantitatif dan kualitatif. Perolehan data kuantitatif melalui angket dengan skala likert. Sementara prolehen data kualitatif didapat melalui kritik dan saran dari ahli materi, media, Al-Qur’an dan subjek peneliti. Buku suplemen digital ini diujicobakan pada 25 siswa yang mencakup kelas X, XI, serta XII IPS 1 MA Plus Al Amin Abung Surakarta Lampung Utara. Hasil pengembangan buku suplemen Geografi digital dari ahli materi mendapat persentase sebesar 88 persen, ahli media 98 persen, serta ahli Al-Qur’an 92 persen. Hasil tersebut memperlihatkan bahwasannya pengembangan buku suplemen digital geografi bermuatan ayat-ayat Al-Qur’an pada materi tata surya sangat layak sehingga dapat dipergunakan dalam pembelajaran Geografi.